Illness Perception in Turkish Schizophrenia Patients: A Qualitative Explorative Study. - Güner, Perihan (Archives of Psychiatric Nursing, 2014)
Background: Schizophrenia is a serious mental illness that is highly complex and not fully understood. Individuals with serious mental illnesses like schizophrenia experience difficulty trying to access mental health services. Few have the opportunity to receive the most optimal evidence-based treatment and only half of those who do actually adhere to the recommended treatment. Understanding what it is like to have this illness would help in our approaches to treatment. Methods: In-depth interviews were conducted on nine Turkish patients with schizophrenia in order to explore the illness from the perspective of patients in remission. Results: Five themes emerged from the patients' descriptions of schizophrenia: schizophrenia is a complicated illness, a mystery, a lost life, a dynamic journey towards recovery, and a developmental process of recovery. Conclusion: This study has identified areas of concern about reflecting the patients' perspectives on their experiences thoroughly, which should help improve healthcare provision and guide future research.